2003
DOI: 10.1152/ajplung.00024.2003
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant lung structure, composition, and function in a murine model of Hermansky-Pudlak syndrome

Abstract: Hermansky-Pudlak syndrome (HPS) is a genetically heterogeneous inherited disease causing hypopigmentation and prolonged bleeding times. An additional serious clinical problem of HPS is the development of lung pathology, which may lead to severe lung disease and premature death. No cure for the disease exists, and previously, no animal model for the HPS lung abnormalities has been reported. A mouse model of HPS, which is homozygously recessive for both the Hps1 (pale ear) and Hps2 (pearl) genes, exhibits striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 54 publications
11
92
1
Order By: Relevance
“…In our prior study we normalized total SP-D immunoblotting data to BAL total protein and total phospholipid. This normalization presented a problem in retrospect because of elevated total protein and reduced total phospholipid in BAL from EPPE mice, as we and others have reported (4,7), leading us to conclude that total SP-D was not altered in the EPPE mice. In the present study we instead reported total SP-D in equivalent volumes of BAL from EPPE mice ( Figure 3) and patients with HPS1 ( Figure 5), and found dramatic differences that progressed with age in EPPE mice, and with disease severity in patients with HPS1.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In our prior study we normalized total SP-D immunoblotting data to BAL total protein and total phospholipid. This normalization presented a problem in retrospect because of elevated total protein and reduced total phospholipid in BAL from EPPE mice, as we and others have reported (4,7), leading us to conclude that total SP-D was not altered in the EPPE mice. In the present study we instead reported total SP-D in equivalent volumes of BAL from EPPE mice ( Figure 3) and patients with HPS1 ( Figure 5), and found dramatic differences that progressed with age in EPPE mice, and with disease severity in patients with HPS1.…”
Section: Discussionmentioning
confidence: 69%
“…The advantage of the EPPE mouse model is that it recapitulates all the features of adult HPS lung disease with the presence of giant lamellar bodies in alveolar epithelial cells, inflammation, and lung remodeling including fibrosis, albeit also in the context of airspace enlargement not reported in human HPS (4,8). The present study uses this animal model to establish the temporal relationships between each facet of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, murine models of HPS-1 (Pale ear) and HPS-2 (Pearl) show activation of alveolar macrophages in the lung, but not in the blood or peritoneum (47,48). Pale ear HPS-1 mice do not develop spontaneous fibrosis, but have higher baseline collagen deposition and show increased inflammation and collagen expression in response to silica challenge (47,49,50). In response to bleomycin, HPS-1 and HPS-2 mice developed fibrosis significantly earlier and to a greater extent than wild-type mice (48).…”
Section: Murine Modelsmentioning
confidence: 99%